Institutional quality and export-led growth: an empirical study - Sathyamoorthy, Vidhya; Tang, Tuck Cheong (Emerald, 2018)
Purpose: The purpose of this paper is to examine the influence of institutional quality on the export-led growth (ELG) with global evidence of a panel of 119 countries. Design/methodology/approach: The research framework looks at the role of exports in promoting growth via. good institutional quality. The methods of testing are panel data approach of causality, and fixed and random effects models. Findings: Empirical results show that good Institutional quality mediates the ELG relationship in general, and middle income group in specific. The legal institutional quality has significant positive impact, whereas political and economic institutional quality have significant negative impact on ELG for all sampled countries. Research limitations/implications: The Kuncic’s (2014) institutional quality data are annually available between 1990 and 2010. Therefore, time series analysis for individual country is bias with 21 observations. And, this study ignores other potential variables such as capital, labor, real exchange rate, and so on, may possibly contribute to omitted-variables bias. Practical implications: Policymakers may well utilize institutional quality reforms either in terms of improving existing institutional quality or enhancing “second-best” institutions as a policy instrument to reap success from export-oriented growth strategies. Originality/value: Existing studies on ELG have ignored institutional quality as a relevant variable. It looks at the three institutional quality indicators, namely political, economic, and legal in ELG framework.